Elderly Dependency Health Care Model in Community, Ban Jandee Sub-District Health Promoting Hospital, Chang Klang District, Nakhon Si Thammarat Province - Phothaworn, Orawan; Sornkeaw, Wittaya; Sriwisit, Sukhumaphorn; Raksanam, Buppha; Kraikeaw, Rattana (Journal of The Royal Thai Army Nurses, 2025)
The action research aimed at the following objectives: 1) to develop a model for caring elderly dependency and 2) to assess a model for the care of elderly dependency health in the community. The target group consists of 280 individuals: 1) 5 staff members from Ban Chandi Sub-district Health Promoting Hospital, 2) 30 elderly representatives from the elderly club and community leader elders, selected using purposive sampling, and 3) 245 community members, selected using systematic sampling. The study period is from February to August 2024. The tools used include a quality assessment questionnaire for the model, knowledge of elderly health care, elderly health care behaviors, and ability to perform daily activities according to the Barthel ADL index. Frequency, percentage, mean, standard deviation, and Paired t-test were used for data analysis. The results from the development of the new model under the acronym “BAN JANDEE” were implemented, consisting of 9 main steps: Basic Care, Assessment, Nutrition Support, Joint Activities, Assistance with Mobility, Nursing Services, Dedicated Follow-ups, Emergency Response, and Education and Training. After implementing the new model, the average scores in areas such as knowledge of elderly health care, health behavior regarding elderly care, and the ability to perform activities of daily living (according to the Barthel ADL Index) significantly increased compared to before, with statistical significance at the .05 level.